Overt Infection with Chronic Bee Paralysis Virus (CBPV) in Two Honey Bee Colonies - Julia Dittes; Marc O. Schäfer; Heike Aupperle-Lellbach; Christoph K. W. Mülling; Ilka U. Emmerich (Veterinary Sciences, 2020)
Chronic Bee Paralysis Virus (CBPV), a widespread honey bee RNA virus, causes massive worker bee losses, mostly in strong colonies. Two different syndromes, with paralysis, ataxia and flight incapacity on one hand and black hairless individuals with shortened abdomens on the other, can affect a colony simultaneously. This case report presents two Apis mellifera carnica colonies with symptoms of paralysis and hairless black syndrome in 2019. Via RT-PCR, a highly positive result for CBPV was detected in both samples. Further problems, such as a Nosema infection and Varroa infestation, were present in these colonies. Therapy methods were applied to colony 1 comprising queen replacement, shook swarm method and Varroa control, whereas colony 2 was asphyxiated after queen loss and colony weakening. After therapy, colony 1 was wintered without symptoms. Beekeeping and sanitary measures can save a CBPV-infected colony, while further complications result in total colony loss.